EXPLORING PSYCHOSUFISM: SPIRITUAL PRACTICES AND THEIR IMPACT ON MENTAL HEALTH AND PSYCHOLOGICAL RESILIENCE - Kharisuddin Aqib; Mahmudi (Program Studi Tasawuf dan Psikoterapi Fakultas Ushuluddin Universitas Annuqayah Guluk-Guluk Sumenep, 2025)
This study aims to explore the concept of psychosufism as an integrative approach that combines spiritual practices within the Sufi tradition with perspectives from modern psychology, and to examine its potential impact on mental health and psychological resilience. In recent decades, growing attention to mental health has encouraged the development of holistic approaches that address not only cognitive and behavioral dimensions but also the spiritual aspects of human experience. Psychosufism offers a conceptual framework that emphasizes spiritual practices such as dhikr (remembrance), tafakkur (contemplation), muhasabah (self-reflection), and tazkiyat al-nafs (purification of the soul) as pathways for enhancing self-awareness, emotional regulation, and the development of meaningful life perspectives. This research employs a qualitative approach using a literature review and conceptual analysis of key sources in the fields of Sufism and psychology. The findings suggest that spiritual practices rooted in the Sufi tradition contribute to psychological well-being through several mechanisms, including the strengthening of self-control, effective stress management, the cultivation of gratitude, and the construction of positive life meaning. Furthermore, the spiritual values embedded in psychosufism demonstrate significant potential in enhancing individuals’ psychological resilience when facing stress, crises, and life challenges. In conclusion, psychosufism can be considered a complementary framework for the development of spiritually integrated mental health interventions. The integration of psychological and spiritual dimensions offers a promising direction for the advancement of more holistic therapeutic and counseling approaches, particularly in societies where religious and spiritual values play a central role. This study also highlights the need for further empirical research to examine the effectiveness of Sufi-based spiritual practices in promoting mental health and psychological resilience.